2020
DOI: 10.21037/tcr-20-845
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers in colon cancer based on bioinformatic analysis

Abstract: cn.Background: Colon cancer is one of the most common cancers in the world. Targeting biomarkers is helpful for the diagnosis and treatment of colon cancer. This study aimed to identify biomarkers in colon cancer, in addition to those that have already been reported, using microarray datasets and bioinformatics analysis.Methods: We downloaded two mRNA microarray datasets (GSE44076 and GSE47074) for colon cancer from the Gene Expression Omnibus (GEO) database and the most recent colon cancer data (COAD) fromThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…However, the converse was not true, as only 13.3% (PPV =13.3%) of samples with high TMB were classified as MSIhigh/dMMR. In addition, patients with low-TMB were associated with MSS/pMMR (96.2%), and these results are consistent with earlier studies (8,32,37).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, the converse was not true, as only 13.3% (PPV =13.3%) of samples with high TMB were classified as MSIhigh/dMMR. In addition, patients with low-TMB were associated with MSS/pMMR (96.2%), and these results are consistent with earlier studies (8,32,37).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we performed a survival analysis of the panel-TMB measured by the GP645 using TCGA database and found that high-TMB patients were strongly associated with poor OS in CRC. Previous studies confirmed that TMB measured by a cancer-related gene panel (CRGP) could be used for prognosis and to predict the benefits of immunotherapy (30)(31)(32). Thus, these findings indicated that higher panel-TMB might be an adverse prognostic factor for CRC.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…DEPDC1, DEP (disheveled, EGL-10, pleckstrin) domain-containing 1 protein, is a novel oncoantigen upregulated in multiple types of cancers, including HCC ( Kanehira et al, 2007 ; Qu et al, 2018 ; Zhao et al, 2019 ; Zhu et al, 2020 ). DEPDC1 is thought to be a novel diagnostic marker for human cancers and a molecular-target for novel therapeutic drugs or cancer peptide-vaccine.…”
Section: Introductionmentioning
confidence: 99%